2019
DOI: 10.1016/j.matpur.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Suitable weak solutions of the Navier–Stokes equations constructed by a space–time numerical discretization

Abstract: We prove that weak solutions obtained as limits of certain numerical space-time discretizations are suitable in the sense of Scheffer and Caffarelli-Kohn-Nirenberg. More precisely, in the space-periodic setting, we consider a full discretization in which the θmethod is used to discretize the time variable, while in the space variables we consider appropriate families of finite elements. The main result is the validity of the so-called local energy inequality.2010 Mathematics Subject Classification. 35Q30,76M10… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…In this paper, we continue and extend some previous works in [3,6,7,8] and especially [5] to analyze the difficulties arising when dealing with full space-time discretization with schemes which are of second order in the time variable. The aim of this paper is to extend to the case θ = 1/2, which corresponds to the Crank-Nicolson method and which could not be treated directly with the same proofs as in [5]. In particular, the case θ = 1/2 requires a coupling between the space and time mesh-size, which is nevertheless common to other second order models.…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…In this paper, we continue and extend some previous works in [3,6,7,8] and especially [5] to analyze the difficulties arising when dealing with full space-time discretization with schemes which are of second order in the time variable. The aim of this paper is to extend to the case θ = 1/2, which corresponds to the Crank-Nicolson method and which could not be treated directly with the same proofs as in [5]. In particular, the case θ = 1/2 requires a coupling between the space and time mesh-size, which is nevertheless common to other second order models.…”
Section: Introductionmentioning
confidence: 71%
“…The interplay between suitable weak solutions and numerical computations of turbulent flows has been emphasized starting from the work of Guermond et al [17,18] and a recent overview can be found in the monograph [4]. In this paper, we continue and extend some previous works in [3,6,7,8] and especially [5] to analyze the difficulties arising when dealing with full space-time discretization with schemes which are of second order in the time variable. The aim of this paper is to extend to the case θ = 1/2, which corresponds to the Crank-Nicolson method and which could not be treated directly with the same proofs as in [5].…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations